"Free butterflies will come out of these deep wounds": A grounded theory of how endometriosis affects women's psychological health. (March 2018) - Facchin, Federica; Saita, Emanuela; Barbara, Giussy; Dridi, Dhouha; Vercellini, Paolo
This study aimed to develop a grounded theory of how endometriosis affects psychological health. Open interviews were conducted with 74 patients. The Hospital Anxiety and Depression Scale was administered to all women, who were divided into distressed versus non-distressed. At the core of our grounded theory was the notion of disruption due to the common features of living with endometriosis. Experiencing disruption (vs restoring continuity) involved higher distress and was associated with a long pathway to diagnosis, bad doctor–patient relationships, poor physical health, lack of support, negative sense of female identity, and identification of life with endometriosis.